Physiological analysis of simple rapid movements in patients with cerebellar deficits. - Mark Hallett; Alfredo Berardelli; J.A. Matheson; John C. Rothwell; C. D. Marsden (1991)
Patients with cerebellar deficits made elbow flexion movements as rapidly as possible for three different angular distances. Electromyographic activity of biceps and triceps and the kinematics of the movements were analysed. Results were compared with those of normal subjects making both rapid and slow movements. In the patients, the first agonist burst of the biceps was frequently prolonged regardless of the distance or speed of the movement. The most striking kinematic abnormality was prolonged acceleration time. The pattern of acceleration time exceeding deceleration time was common in patients but uncommon in normal subjects. The best kinematic correlate of the duration of the first agonist burst was acceleration time. Altered production of appropriate acceleration may therefore be an important abnormality in cerebellar dysfunction for attempted rapid voluntary movements.